2001
DOI: 10.1074/jbc.m104770200
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-related Changes in cAMP Response Element-binding Protein Content Enhance Smooth Muscle Cell Proliferation and Migration

Abstract: We hypothesized that diabetes and glucose-induced reactive oxygen species lead to depletion of cAMP response element-binding protein (CREB) content in the vasculature. In primary cultures of smooth muscle cells (SMC) high medium glucose decreased CREB function but increased SMC chemokinesis and entry into the cell cycle. These effects were blocked by pretreatment with the antioxidants. High glucose increased intracellular reactive oxygen species detected by CM-H 2 DCFA. SMC exposed to oxidative stress (H 2 O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
84
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 54 publications
11
84
1
Order By: Relevance
“…Another key difference between the actions of S100b and high glucose is our present observation for the first time that high glucoseinduced COX-2 also involves the proximal CRE site and activation of CREB. Whereas reports have shown the effects on high glucose on CREB in vascular smooth muscle cells (43) and mesangial cells (44), our results suggest a novel new role for CREB in monocytes. Thus, whereas both AGEs and high glucose can induce COX-2 expression in monocytes, they differ in the molecular mechanisms of regulation.…”
Section: Fig 4 High Glucose (Hg) Stimulates Cox-2 Protein Expressiocontrasting
confidence: 43%
“…Another key difference between the actions of S100b and high glucose is our present observation for the first time that high glucoseinduced COX-2 also involves the proximal CRE site and activation of CREB. Whereas reports have shown the effects on high glucose on CREB in vascular smooth muscle cells (43) and mesangial cells (44), our results suggest a novel new role for CREB in monocytes. Thus, whereas both AGEs and high glucose can induce COX-2 expression in monocytes, they differ in the molecular mechanisms of regulation.…”
Section: Fig 4 High Glucose (Hg) Stimulates Cox-2 Protein Expressiocontrasting
confidence: 43%
“…This is further supported by our data showing that high glucose increases SMC proliferation in culture. Although some previous studies show that high glucose increases SMC proliferation (38,39), in other studies, no mitogenic effects were observed (30 -32). Reasons for such discordance are unclear but may relate to the inability of high glucose to promote growth in the absence of serum or when supra-maximal growth is stimulated by high (5-10%) serum in the growth medium.…”
Section: Discussionmentioning
confidence: 80%
“…Specific primers used for RT-PCR analysis of S1P receptors and sphingosine kinase isoforms were designed essentially as previously described (25). The expected PCR products for S1P 1 , S1P 2 , S1P 3 , S1P 4 , S1P 5 , SK1, and SK2 were 647, 321, 321, 278, 306, 500, and 319 bp, respectively. RT-PCR was performed by using one-step RT-PCR kit (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of occlusive macrovascular disease involves an excessive accumulation of cells within the intima and media (3). Enhanced cell proliferation is believed to be a key feature of diabetic vasculopathy (4,5). However, recent studies clearly suggest that dysregulated cell apoptosis also contributes to the pathogenesis and progression of vascular disease (6,7).…”
mentioning
confidence: 99%